Place of Ukrainian law among other legal systems of the world - Федоров, Валентин Андрійович; Федоров, Валентин Андреевич; Fedorov, Valentyn A.; Тіщенко, Юлія Валеріївна; Тіщенко, Ю. В.; Тищенко, Юлия Валерьевна; Tishchenko, Yuliia V.; Чіпко, Наталія Василівна; Чіпко, Н. В.; Чипко, Наталия Васильевна; Chipko, Nataliia V. (Florencia : Universidad de la Amazonia, 2019)
The relevance of the article is the need to clearly identify the place of Ukrainian law among other legal systems in the world. The study focuses on domestic and foreign legal systems, most notably Romano-Germanic and Anglo-American legal families. The following research methods were used when writing the study: comparative law, analysis, synthesis, induction, deduction, etc. The purpose of this paper is to determine the place of Ukrainian law among other systems of law in the world. To achieve this goal, the following research objectives were set: to analyze the main properties of domestic and foreign legal systems; to determine directions of improvement of the domestic legal system, using the positive experience of foreign countries. The authors conclude that the Ukrainian legal system needs improvement and further integration into the Romano-German legal system. At the same time, some of the past generations of domestic lawyers and scholars deserve to be rethought in the modern era. By providing a starting point for the development of law in the form of already accumulated legal values, the hereditary connections of the considered legal phenomena bring together the past, present, and future, bringing to life new generations of ready-made achievements in the field of law. This condition determines the dynamism of law, its development, exerts a beneficial influence on law-making and law-enforcement processes, as well as defines topical issues of national and international legal development.

Актуальність статті полягає у необхідності чіткого визначення місця українського права серед інших правових систем світу. Об’єктом дослідження є вітчизняна та іноземні системи права, передовсім – романо-германської і англо-американської правових сімей. При написанні дослідження були використані наступні методи дослідження: порівняльноправовий, аналізу, синтезу, індукції, дедукції тощо. Метою даної роботи є визначення місця українського права серед інших систем права у світі. Для досягнення зазначеної мети були поставлені наступні завдання дослідження: проаналізувати головні властивості вітчизняної та іноземних правових систем; визначити напрямки вдосконалення вітчизняної правової системи, використовуючи позитивний досвід іноземних країн. Авторами був зроблений висновок про те, що українська правова система потребує удосконалення і подальшої інтеграції в романо-германську правову систему. В той же час, деякі напрацювання минулих поколінь вітчизняних юристів і науковців заслуговують на їхнє переосмислення у сучасний період. Забезпечуючи вихідну базу для розвитку права в вигляді вже накопичених правових цінностей, спадкоємні зв'язки розглянутих правових явищ з'єднують воєдино минуле, сьогодення і майбутнє, вводять в життя нових поколінь вже готові досягнення у галузі права. Такий стан обумовлює динамічність права, його розвиток, здійснює благотворний вплив на правотворчий і правозастосовний процеси, а також визначає актуальні питання національного й міжнародно-правового розвитку.
Fedorov V. Place of Ukrainian law among other legal systems of the world / V. Fedorov, N. Chipko, Y. Tishchenko // Amazonia Investiga. - Vol. 8. - Issue 23. - Florencia : Universidad de la Amazonia, 2019. - P. 76-80.
Keywords: legal regulation; legal family; system of law; legal system; legal norm; правове регулювання; правова сім’я; система права; правова система; норма права; Research Subject Categories::LAW/JURISPRUDENCE